A Novel Candidate for Prevention and Treatment of Atherosclerosis: Urolithin B Decreases Lipid Plaque Deposition in apoE−/− Mice and Increases Early Stages of Reverse Cholesterol Transport in ox‐LDL Treated Macrophages Cells. Issue 10 (26th April 2019) - Zhao, Wenhua; Wang, Lixue; Haller, Viktoria; Ritsch, Andreas
Abstract : Scope: HDL cholesterol is inversely related to the incidence of atherosclerosis. Polyphenols including ellagitannins have been shown to exert antiatherogenic properties. Urolithin B is formed from ellagitannins by components of the gut microbiota, and urolithins might be involved in beneficial effects against cardiovascular diseases in vitro. In this study, the influence of urolithin B on several parameters involved in the lipid plaque deposition and the reverse cholesterol transport is investigated. Methods and results: In apoE −/− mice and two different macrophage cell lines, the influence of urolithin B and its phase II conjugated metabolite on lipid plaque deposition, cholesterol uptake, and expression of ABCA1 and SR‐BI is tested. It is shown that urolithin B decreases lipid plaque deposition, both urolithin B and urolithin B sulfate modulate expression of SR‐BI and ABCA1, and cholesterol efflux increases from cholesterol laden macrophages to HDL particles as well as to reverse lipid uptake by stimulated THP‐1 macrophages. Conclusions: Urolithin B can decrease lipid plaque deposition, and urolithin B and urolithin B sulfate are able to induce reverse cholesterol transport by influencing expression of key proteins of this pathway. Urolithin B may represent the basis for development of new drugs for prevention and treatment of atherosclerosis in humans. Abstract : Urolithin B decreases lipid plaque deposition in apoE −/− mice. Urothilin B sulfate not only induces expression of SR‐BI and ABCA1 in J774 and THP‐1 macrophages but also is able to reverse the ox‐LDL down‐regulated expression of SR‐BI and ABCA1 in these cells.